KAJIAN RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA ANAK DENGAN INFEKSI SALURAN KEMIH DI RSUD Dr. MOEWARDI SURAKARTA - Agustiningrum, Frisda Ayu; Amrullah, Adhi Wardhana; Rahardjoputro, Rolando (Jurnal Buana Farma, 2024)
Urinary tract infection (UTI) is the second highest infectious disease among children in Indonesia. Management of UTI requires antibiotic therapy, but the irrational use of antibiotics makes this disease one of the contributors to the high rate of antibiotic resistance. Therefore, there is a need for a study to measure the rationality of antibiotic use in children with UTI. This study is a descriptive observational study with a cross sectional design. Data were collected retrospectively using a purposive sampling technique based on medical record data of pediatric patients at Dr. Moewardi Surakarta Hospital in 2021-2023. The results showed that out of 100 medical records of pediatric patients with UTI, 68.00% were women and 32.00% were men. Based on age, the highest incidence of UTI occurred in the age range of 10-18 years as much as 52.00%. The most common antibiotic use was ampicillin 68.00%. The results of the rationality study showed 69.00% in category 0 (rational use of antibiotics). Irrationality occurred in category IIA (antibiotic use is not the right dose) 17.00%, IIIA (antibiotic use with too long duration) 1.00%, IIIB (antibiotic use with too short duration) 4.00%, IIA & IIIB (antibiotic use is not the right dose & duration is too short) 2.00%, IVA (there are other more effective antibiotic options) 4.00%, IIIB & IVA (antibiotic use is too short duration & there are other more effective antibiotic options) 3.00%. It can be concluded that the rational use of antibiotics needs to be improved.